An evaluation of social responsibility initiatives on HIV/AIDS in the workplace : a case study of the Kwazulu-Natal South African Social Security Agency (SASSA-KZN) - Nxaba, Siphosenkosi Blessing (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Industrial Psychology))--University of Stellenbosch, 2009.